POTENSI PENGEMBANGAN USAHA RUMAH TANGGA PETANI SAGU (Metroxylon) DI KAMPUNG NENDALI DISTRIK SENTANI TIMUR KABUPATEN JAYAPURA - Tangkelayuk, Herman; Resubun, Ratna Luciana (Jurnal Pertanian Terpadu Santo Thomas Aquinas, 2022)
This research was conducted in Nendali Village, East Sentani District, Jayapura Regency. Respondents used in this study were 18 heads of families (KK) who work as sago farmers. The purpose of this study was to determine the costs incurred and find out how much income the sago farmers earn in Nendali Village, East Sentani District, Jayapura Regency. Based on the results of this study, it can be concluded that the total cost of household business of sago farmers incurred up to the production stage of 18 families (KK), is Rp. 17,600,000, while the average incurred by farmers is Rp. 977,777 then the total income for 18 families (KK) of sago farmers is Rp. 36,200,000 with an average of Rp. 2,011,111. From the results of this study, it is necessary to suggest to farmers to be able to carry out sago tree cultivation, so that sago trees do not become extinct so that in terms of production will increase.